SPORT TERMINOLOGY IN LINGUISTICS - Marupova Gulnaz Umarjonovna (International Journal of Literature and Language Studies, 2026)
Sport terminology constitutes a significant part of modern vocabulary and reflects the interaction between language, culture, and society. The language of sport has developed into a specialized subsystem characterized by specific lexical, semantic, and pragmatic features. This article examines the concept of sport terminology from a linguistic perspective, its classification, formation processes, and functions in contemporary communication. Particular attention is paid to the role of borrowing, metaphorization, and globalization in the development of sports vocabulary.